Demystifying the Empowerment Virtues of the New Digital World Information Order - Mattelart, Tristan (Javnost-The Public, 2015)
Despite being highly ambiguous, the vocabulary of empowerment has been used recurrently since the early 2000s for celebrating the emancipatory potential of digital technologies. Indeed, these have been repeatedly described as having the power of bypassing the controls that authoritarian governments exert on the circulation of news, but also of circumventing the domination that corporate actors exercise in this field.